1967
DOI: 10.1136/bmj.3.5557.90
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of urinary infection by means of closed drainage into a sterile plastic bag.

Abstract: Intermittent Haemodialysis-Clunie et al.BRIT was an obvious mechanical cause. If flow was still unsatisfactory after attempted declotting, clots were occasionally dislodged or vessel spasm was overcome by the slow infusion of a solution of 20,000 international units of heparin in 500 ml. of saline. Angiograms were performed by the injection of 3 to 4 ml. of 60% Urografin via the open end of the cannula (Fig. 3) in resistant cases. An attempt was then made to dissolve visualized clot by the injection of 250,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1970
1970
1992
1992

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…Increased tolerance of Gram-negative bacteria to these antiseptics has also been reported by Soprey and Maxcy (1968). Organisms resistant to chlorhexidine have been reported by Gillespie et al (1967), Stickler (1974), andMaurer (1974). Stickler found that four transfers induced significant resistance in Proteus mirabilis, while Maurer found three transfers at weekly intervals sufficient in the case of Ps.…”
Section: Discussionmentioning
confidence: 90%
“…Increased tolerance of Gram-negative bacteria to these antiseptics has also been reported by Soprey and Maxcy (1968). Organisms resistant to chlorhexidine have been reported by Gillespie et al (1967), Stickler (1974), andMaurer (1974). Stickler found that four transfers induced significant resistance in Proteus mirabilis, while Maurer found three transfers at weekly intervals sufficient in the case of Ps.…”
Section: Discussionmentioning
confidence: 90%
“…The particular situation that the organism seems to favour, the urinary tract that is undergoing instrumentation, is one where it is likely to be exposed to antiseptics (Gillespie et al, 1967;Desautels, 1969;Stickler et al, 1971). It would therefore be of considerable ecological advantage to this organism to have a degree of resistance to such antibacterial agents.…”
mentioning
confidence: 99%
“…In addition it has been claimed that despite its extensive use, there have been no reports to indicate the development of bacterial resistance to chlorhexidine (Longworth, 1971). Gillespie, Lennon, Linton, and Phippen (1967), however, isolated strains of Proteus mirabilis from postoperative urinary infections in gynaecological patients undergoing catheterization of the bladder, a procedure which involved the repeated application of chlorhexidine to the urethra, and reported that 10 out of 12 of these strains had minimum inhibitory concentration (MIC) values of 125 to 500 ,tg chlorhexidine/ml, well above the level of 10 to 50 ,ug/ml generally required to inhibit Gram-negative bacteria (Davies et al, 1954).…”
mentioning
confidence: 99%